Research on Safety Resilient Space Design Strategies in Coastal Zone - WAN Xiangyi; JING Wanli; LI Li (Haiyang Kaifa yu guanli)
In the face of the increasingly severe impact of global climate change, the coastal zone, as the region most strongly affected by natural disasters, puts forward higher requirements for its safety resilient. It is urgent to change the traditional single-project safety defense thinking and enhance the adaptability of the coastal zone to cope with various disasters and risks. This paper reviews the risks and challenges that need to be solved in building safety resilient urban areas in coastal zones, draws on the experience of coastal disaster prevention in similar areas abroad, and puts forward strategic suggestions for adapting to the safety resilient space design of China's coastal zones from three aspects of “resilient chathis-defense system-lifeline system”, with a view to providing references for the safety resilient space design of other coastal areas.